2013
DOI: 10.3945/ajcn.112.045245
|View full text |Cite
|
Sign up to set email alerts
|

Eating attentively: a systematic review and meta-analysis of the effect of food intake memory and awareness on eating

Abstract: Evidence indicates that attentive eating is likely to influence food intake, and incorporation of attentive-eating principles into interventions provides a novel approach to aid weight loss and maintenance without the need for conscious calorie counting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
186
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(203 citation statements)
references
References 46 publications
13
186
2
2
Order By: Relevance
“…For example, while automaticity (i.e., being unaware or inattentive), impulsivity, and emotional distress are noted in current literature to contribute toward the current obesity epidemic (see Cohen and Farley 2008;Elfhag and Morey 2008;Nederkoorn et al 2006), other research has shown that mindfulness relates negatively to automatic, emotional, and impulsive reactions (Brown and Ryan 2003;Goldin and Gross 2010;Lattimore et al 2011;Levesque and Brown 2007;Sloan 2004;WenkSormaz 2005) and positively to self-regulation (Lakey et al 2007; Levesque and Brown 2007). Furthermore, a systematic review and meta-analysis on attention and memory as potential determinants of eating behavior revealed that incorporating attentive-eating principles into mainstream interventions are a novel way to aid weight loss (Robinson et al 2013), which makes mindfulness training an even more relevant method of aiding people who are struggling to lose weight. But mindfulness is not only about attentional training.…”
Section: Introductionmentioning
confidence: 92%
“…For example, while automaticity (i.e., being unaware or inattentive), impulsivity, and emotional distress are noted in current literature to contribute toward the current obesity epidemic (see Cohen and Farley 2008;Elfhag and Morey 2008;Nederkoorn et al 2006), other research has shown that mindfulness relates negatively to automatic, emotional, and impulsive reactions (Brown and Ryan 2003;Goldin and Gross 2010;Lattimore et al 2011;Levesque and Brown 2007;Sloan 2004;WenkSormaz 2005) and positively to self-regulation (Lakey et al 2007; Levesque and Brown 2007). Furthermore, a systematic review and meta-analysis on attention and memory as potential determinants of eating behavior revealed that incorporating attentive-eating principles into mainstream interventions are a novel way to aid weight loss (Robinson et al 2013), which makes mindfulness training an even more relevant method of aiding people who are struggling to lose weight. But mindfulness is not only about attentional training.…”
Section: Introductionmentioning
confidence: 92%
“…In our study, however, changing the physical context had no positive effect on meal enjoyment or on food intake. Regarding the music condition, it was demonstrated that reducing attention via distraction during eating (such as listening to radio drama or watching television) increases food intake in the younger population (Robinson et al, 2013). In the present experiment, the experimenter asked the residents to choose from a list the music they wished to hear throughout the meal.…”
Section: Surroundingmentioning
confidence: 98%
“…Highly processed foods are defined as multi-ingredient, industrially formulated mixtures (17). Some, but not all, processed foods are manufactured to be ready-to-eat (RTE) 4 and may independently promote overconsumption; thus, researchers may distinguish processing from convenience (19)(20)(21)(22). The highly processed and RTE foods purchased by US households were found to have substantially higher saturated fat, sugar, and sodium content than less processed foods or foods requiring cooking, respectively (17).…”
Section: Introductionmentioning
confidence: 99%